Empowerment of Local Fishermen Groups in Environmental Management Activities - Qadir, Muhammad Muhtaj (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
The purpose of this study was to determine: (1) Description of the participation of fishermen groups in the coral reef rehabilitation activities in Baurung Village and (2) The factors that most influenced fishermen groups to participate during the implementation of the coral reef rehabilitation activities in Baurung Village. This study uses a mixed approach (Mix Method), which is a combination of qualitative and quantitative methods. The study population was 22 fishermen who were involved in the coral reef rehabilitation activities in Baurung Village. Quantitative data collection techniques will be obtained from structured interviews using a questionnaire or questionnaire. The data analysis used multiple regression analysis at the significance level Î± = 0.05. The results of this study are that there is a significant influence between age, education level, type of work, income level, leadership, institutional formation, the role of government and mentoring on participation in the coral reef rehabilitation activities as evidenced by the Sig value. F is 0.000 <0.05 and the Fcount value is greater than Ftable (22.050> 2.77). The conclusions of this study were (1) The description of the participation of fishermen groups has decreased symptoms at the monitoring and maintenance activities stage (6.9%) was influenced by other variables not used in this study; (2) The factor that most influenced fishermen groups in participating during the implementation of the coral reef rehabilitation activities in Baurung Village was the role of the government at 28.72%.